2021
DOI: 10.1186/s12889-021-10708-w
|View full text |Cite
|
Sign up to set email alerts
|

Health, psychosocial, and economic impacts of the COVID-19 pandemic on people with chronic conditions in India: a mixed methods study

Abstract: Background People with chronic conditions are disproportionately prone to be affected by the COVID-19 pandemic but there are limited data documenting this. We aimed to assess the health, psychosocial and economic impacts of the COVID-19 pandemic on people with chronic conditions in India. Methods Between July 29, to September 12, 2020, we telephonically surveyed adults (n = 2335) with chronic conditions across four sites in India. Data on participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
90
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(115 citation statements)
references
References 50 publications
5
90
0
1
Order By: Relevance
“…Lastly, as indicated by previous studies, low SES is a major underlying factor for psychosocial distress and response to the pandemic. 24 Therefore, further research is warranted to shed light on the long-term psychological, health and socioeconomic impacts of COVID-19 pandemic among vulnerable or marginalised population. 25 26 …”
Section: Discussionmentioning
confidence: 99%
“…Lastly, as indicated by previous studies, low SES is a major underlying factor for psychosocial distress and response to the pandemic. 24 Therefore, further research is warranted to shed light on the long-term psychological, health and socioeconomic impacts of COVID-19 pandemic among vulnerable or marginalised population. 25 26 …”
Section: Discussionmentioning
confidence: 99%
“…Social distancing might be necessary to contain these deadly pathogens, but it comes with panic and socio-economic collapse [41]. However, considering vaccination, pandemic control measures, and the re-emergence of new variants, global economic activity might reduce to 4% in 2021 and 3.8% in 2022, or on the darker side, might face downfall with below-potential growth by 2022 if the situation becomes worse [17,19,33]. Additionally, due to lockdown and other restrictions, mental health would wither away mainly because of unemployment, which may also lead to crime, burglary, and fraud business [42][43][44][45].…”
Section: Possible Social Complications Of Outbreaks In the Near Futurementioning
confidence: 99%
“…A study by Shammi et al, 2021 [18], revealed the impact of COVID-19 in Bangladesh on gender discrimination, gender-based violence, business, economy, and education sectors, which was supported by another study by Singh et al, 2021 [19], in India who reported that 59%, 38%, and 28% of people lost job, income, and food security, respectively, due to the surge of ongoing COVID-19 in 2021. This socio-economical scenario can be seen everywhere around the world [17][18][19][20]. Moreover, due to the death of 3,538,764 people around the world, it has already affected the amount of working manpower, mainly in food and other basic industrial levels [10,11,[17][18][19][20].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, since the emergence of severe acute Viruses 2021, 13, 1179 2 of 15 respiratory syndrome coronavirus 2 (SARS-CoV-2) in December 2019 [4,5], there were about 91 million confirmed infections and 2 million deaths worldwide as of 14 January 2021 [6]. The COVID-19 pandemic has been generating health, economic, and social crises worldwide [7]. Given that multiple viruses are the causative agents of human respiratory infection and co-infection has been continuously reported, the development of a novel treatment modality that has a broad-spectrum antiviral effect is urgently needed.…”
Section: Introductionmentioning
confidence: 99%